2020
DOI: 10.1007/s40615-020-00877-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Human Papillomavirus Vaccine Uptake Among Racial/Ethnic Minorities: a Systematic Review

Abstract: Background: Human papillomavirus (HPV) is associated with poor health outcomes, including cervical cancer. Racial/ethnic minority populations experience poor health outcomes associated with HPV at higher rates. A vaccine is available to protect against HPV infections and prevent HPV-related sequelae; however, vaccination rates have remained low in the United States (U.S.) population. Thus, there is an urgent need to increase HPV vaccination rate. Moreover, little is known about barriers to HPV vaccination in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…Additionally, a recent study found that Black adults reported greater hesitancy to get vaccinated for COVID-19 compared to non-Hispanic Whites [ 13 ]. This is consistent with research showing lower rates of vaccine uptake among racial and ethnic minorities [ 14 , 15 ]. In order to address the continued disproportionate burden of COVID-19 on communities of color, greater attention and appropriate strategies to mitigate barriers to care, such as medical mistrust, are needed.…”
Section: Introductionsupporting
confidence: 91%
“…Additionally, a recent study found that Black adults reported greater hesitancy to get vaccinated for COVID-19 compared to non-Hispanic Whites [ 13 ]. This is consistent with research showing lower rates of vaccine uptake among racial and ethnic minorities [ 14 , 15 ]. In order to address the continued disproportionate burden of COVID-19 on communities of color, greater attention and appropriate strategies to mitigate barriers to care, such as medical mistrust, are needed.…”
Section: Introductionsupporting
confidence: 91%
“…Decision making about vaccine uptake and completion is a multilayered process that involves comparing the perceived benefits of the vaccine against its perceived risks. Among vaccine refusers, reasons commonly included not only lack of trust in the healthcare provider, but also inadequate or inaccurate knowledge about the pros and cons of the vaccine [45] . Indeed, misinformation spread on social media and the internet is a concern as these messages can directly impact HPV vaccine decisions [46] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Strategic elements to assist in global vaccination efforts include financial investment on a global level, enhancement of supply, single dose schedules, and effective social marketing [24]. Use of social media platforms to increase awareness of the notion that a vaccine preventable cancer such as cervical cancer may be the wave of the future.…”
Section: Author Detailsmentioning
confidence: 99%